The autonomy principle in companion veterinary medicine: A critique - Hiestand, Karen M. (Frontiers in Veterinary Science, 2022)
Following developments in human medical ethics, veterinary ethics has similarly shifted from a historic paternalistic approach toward greater respect for autonomy. Veterinarians operate within a tripartite system where there is separation of doctor/patient dyad by animal owners. As such there are fundamental differences between veterinary and human medical sectors regarding application of the autonomy principle – specifically, to whom is autonomy afforded? This paper argues that the accepted transference of autonomy to owners constitutes a corruption of the principle. Privileges owners exercise over animal treatment decisions relate to their rights over property use, rather than application of self-rule over one’s own person as described in bioethics literature. To highlight issues with the status quo, this paper outlines the negative consequences of ‘owner autonomy’ on animal (patient) welfare, integrity of the veterinary profession’s social contract and professional autonomy. A way forward is proposed that places greater emphasis on animal (patient) welfare being explicitly at the centre of veterinary treatment decision-making via recognition that all such decisions are made by a proxy and therefore, more appropriate frameworks than autonomy ought to be engaged, such as a best interests paradigm.